Pedestrian Traffic Stress Levels (PTSL) in School Zones: A Pedestrian Safety Assessment for Sustainable School Environments-Evidence from the Caferağa Case Study - Yilmaz, Yunus Emre; Gursoy, Mustafa (MDPI, 2026)
Pedestrian safety in school zones is shaped by traffic conditions and street design characteristics, whose combined effects involve uncertainty and gradual transitions rather than sharp thresholds. This study presents an integrated assessment framework based on the analytic hierarchy process (AHP) and fuzzy logic to evaluate pedestrian traffic stress level (PTSL) at the street-segment scale in school environments. AHP is used to derive input-variable weights from expert judgments, while a Mamdani-type fuzzy inference system models the relationships between traffic and geometric variables and pedestrian stress. The model incorporates vehicle density, pedestrian density, lane width, sidewalk width, buffer zone, and estimated traffic flow speed as input variables, represented using triangular membership functions. Genetic Algorithm (GA) optimization is applied to calibrate membership-function parameters, improving numerical consistency without altering the linguistic structure of the model. A comprehensive rule base is implemented in MATLAB (R2024b) to generate a continuous traffic stress score ranging from 0 to 10. The framework is applied to street segments surrounding major schools in the study area, enabling comparison of spatial variations in pedestrian stress. The results demonstrate how combinations of traffic intensity and street geometry influence stress levels, supporting data-driven pedestrian safety interventions for sustainable school environments and low-stress urban mobility.
Keywords: sustainable school environments; pedestrian safety; school zones; pedestrian traffic stress level; fuzzy logic; analytic hierarchy process; URBAN-ENVIRONMENT; SERVICE; INTERSECTIONS; WALKING; Science & Technology - Other Topics; Environmental Sciences & Ecology